The siege of the city of Thessaloniki and its fall by the Ottomans Between 1422-1430 - Zoukar , Suhail; laika , Nadeem (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The city of Thessaloniki became under the control of the Ottomans and remained in their hands from 1387 until 1403, after the Battle of Ankara and the Treaty of Gallipoli, which resulted in the Turks giving up the city for the Byzantines, but with the arrival of Murad II, who entered a conflict with his brother, Mohammed Shalabi in 1422, where supported the Byzantines Muhammad against his brother Murad Murad after he took control of the Ottoman Empire on the siege of Salonika and wanted to regain control at a time when the city suffers from lack of resources to defend it. In early 1430, Sultan Murad II besieged Thessaloniki with large numbers of soldiers. The siege of the city led to hunger, death and the emigration of large numbers of inhabitants. The Ottomans then took control of the city and the Venetian Treaty of Peace was signed by the Ottomans. Take control of Albania.